2020
DOI: 10.1002/fsn3.1975
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of flavored milk containing bitter orange peel extract and Gaz‐angubin

Abstract: In this study, the effects of adding Gaz‐angubin at three different levels (5%, 10%, and 15% w/v) and bitter orange peel extract with three different concentrations (0.025%, 0.050%, and 0.075% w/v) on selected characteristics of the flavored milk were investigated during 10‐day storage at 4°C. The results showed that increasing the level of Gaz‐angubin and bitter orange peel extract increased viscosity, antioxidant activity, and total polyphenol content, decreased total microbial count, and improved the sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Aqueous orange peel extract had many food applications such as supplementation in minced beef to suppress lipid oxidation [ 18 ] and milk for increasing the antioxidant activity and total polyphenol content, and decreasing the total microbial count [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aqueous orange peel extract had many food applications such as supplementation in minced beef to suppress lipid oxidation [ 18 ] and milk for increasing the antioxidant activity and total polyphenol content, and decreasing the total microbial count [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peels tend to be the predominant byproduct of citrus juice production, contributing to environmental contamination [ 19 ]. Over 100 million tons of citrus fruit is harvested every year, making it the world’s most prolific fruit crop.…”
Section: Introductionmentioning
confidence: 99%
“…Physicochemical properties and sensorial acceptance of strawberry‐flavored milk declined with the increase in time (Hossin et al., 2021). Jalilzadeh‐Afshari and Fadaei, (2021) reported that increasing the Gaz‐angubin content and bitter orange peel extract in flavored milk improved sensorial properties, viscosity, antioxidant activity, and total polyphenol content, while decreased total microbial count. The best flavored milk sample contained 15% Gaz‐angubin and 0.075% bitter orange peel extract (Jalilzadeh‐Afshari & Fadaei, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Jalilzadeh‐Afshari and Fadaei, (2021) reported that increasing the Gaz‐angubin content and bitter orange peel extract in flavored milk improved sensorial properties, viscosity, antioxidant activity, and total polyphenol content, while decreased total microbial count. The best flavored milk sample contained 15% Gaz‐angubin and 0.075% bitter orange peel extract (Jalilzadeh‐Afshari & Fadaei, 2021). Patel et al., (2020) formulated value‐added flavored buffalo milk and pumpkin pulp.…”
Section: Introductionmentioning
confidence: 99%
“…The flavoured milk samples that contained 15 percent Gaz-angubin and 0.075 percent bitter orange peel extract claimed to have the highest overall acceptability score, the highest percentage of inhibition of free radicals, the lowest total microbial count, and the lowest total polyphenol content (TPC). These samples also had the lowest total microbial count (TMC) (Jalilzadeh-Afshari and Fadaei, 2021).…”
Section: Introductionmentioning
confidence: 99%